(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Essential oil compositions of the inflorescences and leaf of Piper longum Linn. were investigated by gas chromatographymass spectrometry (GC-MS). P. longum oils were found to contain few monoterpene hydrocarbons, a moderate content of sesquiterpenes and high content of aliphatic hydrocarbons. The inflorescences oil rich in eugenol (33.11%), caryophyllene (9.29%), cinnamyl acetate (5.91%) and b-pinene (4.74%), whereas leaf oil rich in trans-nerolidol (19.08%), caryophyllene (12.25%), 3-heptene, 7-phenyl- (3.71%), benzyl benzoate (3.68%), caryophyllene oxide (3.62%) and ?-elemene (3.28%). The compositions of both oils varied qualitatively and quantitatively. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13408 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):77-85, 2008